Faster farmer replacement of improved wheat varieties provides resilience and income; laid a foundation for Ethiopian wheat self-sufficiency - CGIAR Research Program on Wheat (2018)
Building on past successes facilitating adoption of improved wheat seed with higher on farm yields, and support for disease monitoring and diagnostics, CGIAR (WHEAT, PIM) researchers identified necessary conditions to allow farmers to more rapidly replace traditional varieties with improved varieties. This contributes to improved resilience and incomes among Ethiopian wheat farmers, and laid a foundation for Ethiopia's goal of wheat self-sufficiency.